Audit Layanan Tata Kelola Informasi Rumah Sakit St. Carolus Menggunakan COBIT 2019 - Reynaldi Widarja; Besus Maula Sulthon (STMIK Budi Darma, 2023)
Technological advancements are rapidly evolving, particularly in organizations or businesses that heavily rely on valuable information to enhance their strategies. St. Carolus Hospital has integrated an HIS (Hospital Information System) to harness the power of information technology. The vision of St. Carolus Hospital is “To become a trusted family health partner that provides international standard medical and nursing services, supported by appropriate medical & digital technology, by 2025.”. Effective management of information data enables companies to gain insights into industry trends and the progress of other organizations within their respective fields. COBIT 2019 provides a comprehensive framework designed to assist organizations in planning, implementing, monitoring, and evaluating their information technology. Following the analysis, specific evaluation objectives were identified, namely APO02 – Managed Strategy, APO03 – Managed Enterprise Architecture, and DSS06 – Managed Business Process Controls. Based on the capability level evaluation, both APO02 and APO03 achieved level 2, indicating operational processes that have achieved their goals but fell short of expectations. On the other hand, DSS06 reached level 3, indicating the usage of a defined process in achieving results, despite some processes not being fully operational. Thus, these three domains require improvement based on the discovered gaps to reach the expected level.